Assessment of knowledge in oncology about care for transgender people: a scoping review - Fernanda Fachetti Xavier de Almeida; Cremilson de Paula Silva; Ricardo Souza Evangelista Sant’Ana; Ruan Nilton Rodrigues Melo (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to identify evidence available in the literature on instruments and methodologies used to assess healthcare professionals’ knowledge about cancer care for the transgender population. Methods: a scoping review was conducted in seven databases, including studies that answered the question: what is the healthcare professionals’ level of knowledge about cancer care for the transgender population? Results: forty-one articles were selected that dealt specifically with healthcare professionals’knowledge in relation to care for the LGBTQIAPN+ population, especially the transgender population. Eighteen studies assessed patients’ perceptions of professionals’knowledge, whereas other studies used their own assessment tools, considering the global context of LGBTQIAPN+ health. Conclusions: there is no tested and validated instrument that assesses the knowledge about the transgender population’s oncological health, highlighting the need to construct and validate an instrument focused on this population’s needs.